'Evidence' within local authority decision making. (8th March 2021) - Cook, Michael
Abstract: Michael Cook looks at the role of an embedded Public Health Information Specialist highlighting the ways the core evidence, information and knowledge skills are used to progress Public Health activity in local government settings. Acknowledging the current pandemic, he explores how COVID‐19 has dominated all aspects of health and social care, and outlines how evidence services have work within these complex Public Health systems to lead the local response and recovery efforts.